2014
DOI: 10.1097/ncc.0000000000000099
|View full text |Cite
|
Sign up to set email alerts
|

Physician and Nurse Beliefs of Phase 1 Trials in Pediatric Oncology

Abstract: Background In order to improve the survival of children with cancer, novel therapies must be identified. Promising agents are tested in Phase I trials in order to identify appropriate dosing and describe toxicity in children. The identification and referral of candidate patients for Phase I trials relies heavily on medical providers who must balance their own perceptions of Phase I trials with the desires and willingness of the patient and his/her family. Objective The goal of the present study was to evalua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 7 publications
1
8
0
Order By: Relevance
“…This study was in an agreement with the study done by Barnes, et al who studied physician and nurse beliefs of phase 1 trials in pediatric oncology and found that the majority of the studied sample were had a bachelor degree [10].…”
Section: Discussionsupporting
confidence: 82%
“…This study was in an agreement with the study done by Barnes, et al who studied physician and nurse beliefs of phase 1 trials in pediatric oncology and found that the majority of the studied sample were had a bachelor degree [10].…”
Section: Discussionsupporting
confidence: 82%
“…quiet locales and open areas. 41,[66][67][68][69][70][71][72][73][74][75][76] A majority of qualitative studies fail to account for potential bias from researchers. Only three qualitative studies validated the findings, using focus group interviews 41,71 or documentary analysis for triangulation.…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
“…23,39,40,48,76,112,113,119 Young people, health professionals, and families express the need for children to experience fun, humour, laughter, recreation, and leisure alongside treatment. 23,27,68,76,104,112,113 Family relation concerns have been highlighted in 20 studies. 19,[39][40][41][42]47,48,54,59,63,74,86,88,108,[120][121][122][123][124][125][126] Young people value support from their families as it is a structure that helps them feel comfortable and secure.…”
Section: Psychological (N=65 Studies 80%)mentioning
confidence: 99%
“…5 The nurse practitioner presents innumerable responsibilities related to the care of pediatric oncology patients, considering the periods of intense interactions, which impacts the team, patient and family decision processes. 6 In this sense, seeking to know the role of nurses in the management of childhood cancer within primary care, it was decided to investigate, as the object of study, the nurse practitioner's role in this context. This study is justified by the exponential growth of cancer cases in the world population, including children, and by the scarcity of studies related to the subject, mainly at the national level.…”
Section: Integrative Review Articlementioning
confidence: 99%